2020
DOI: 10.3390/cells9020486
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the microRNA-200 Family, microRNA-205, and Markers of Epithelial–Mesenchymal Transition as Predictors for Endoscopic Submucosal Dissection over Esophagectomy in Esophageal Adenocarcinoma: A Single-Center Experience

Abstract: Endoscopic submucosal dissection (ESD) is an effective treatment of early esophageal adenocarcinomas (EACs). The decision of ESD over esophagectomy is based on clinical evaluation of tumor depth and invasion. On a molecular level, tumor invasion is strongly associated with epithelial-to-mesenchymal transition (EMT). Here, we investigated whether localized ESD-resected and surgically resected EAC samples displayed different expression profiles of EMT protein and microRNA markers and whether these different expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Interestingly, one study reported that epithelial-to-mesenchymal transition (EMT) is associated with the progression from early EAC to invasive EAC. The measurement of EMT markers prior to intervention may help to make the clinical decision between endoscopic submucosal dissection or esophagectomy as the preferred treatment [84]. Cytokines and chemokines are important components of the tumor microenvironment.…”
Section: Biology and Immunologymentioning
confidence: 99%
“…Interestingly, one study reported that epithelial-to-mesenchymal transition (EMT) is associated with the progression from early EAC to invasive EAC. The measurement of EMT markers prior to intervention may help to make the clinical decision between endoscopic submucosal dissection or esophagectomy as the preferred treatment [84]. Cytokines and chemokines are important components of the tumor microenvironment.…”
Section: Biology and Immunologymentioning
confidence: 99%
“…Markers for epithelial mesenchymal transition (EMT) are of clinical relevance for a more targeted treatment 38 . The process of EMT enables cancer cells to enter the blood stream and form local and distant metastasis 39 .…”
Section: Technical Validationmentioning
confidence: 99%
“…Similarly, two of the most reported downregulated miRNAs in EAC, HGD, and/or NDB are hsa-miR-203a-3p 46 51 and hsa-miR-205-5p 45 47 , 50 52 . The latter miRNA (hsa-miR-205-5p) is known for targeting ZEB1 38 . In our dataset, we confirm the differential expression patterns of these miRNAs in disease tissue compared to healthy tissue (Fig.…”
Section: Technical Validationmentioning
confidence: 99%